What is Sarbanes-Oxley? - Lander, Guy P. (McGraw - Hill, 2004)
The Sarbanes-Oxley Act is unquestionably important to corporate America. It can also be complex and confusing, for everyone from the employees who must be doubly aware of what they can--and cannot--do to the officers who must take legal responsibility for the actions, errors, and omissions of those employees. What is Sarbanes-Oxley? provides you with a plain-English overview of the Act to help ensure that your firm achieves and maintains top-to-bottom Sarbanes-Oxley Act (SOA) compliance. Written in clear, concise, and readable language, with helpful checklists so that no requirements are overlooked ...